2006
DOI: 10.1080/17450120600659051
|View full text |Cite
|
Sign up to set email alerts
|

The effects of adult morbidity and mortality on household welfare and the well-being of children in Soweto

Abstract: This is the first description of the effects of adult morbidity and mortality on children residing in Soweto, an urban African setting in South Africa, in the era of HIV/AIDS. We conducted a prospective cross-sectional household survey in Soweto identified by a stratified, two-stage cluster sample. In total, 4912 households were surveyed: 4501 households with children and 411 households with no children under the age of 16 years. We present detailed information on 22 724 individuals. Forty-four per cent of all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Illness and death of a parent will affect any child deeply, but especially infants and preschool children who are entirely dependent on their primary caregivers [27]. Studies have demonstrated comparatively poor health among young children with caregivers unwell with HIV/AIDS [28],[29], and under-nutrition has been identified as the key underlying cause of children's deaths, especially in relation to infectious disease [30]. Thus, when a mother becomes very ill and is unable to care for and feed her child, whether by breastfeeding or providing substitute or complementary feeding, the risks to the child rise substantially.…”
Section: Discussionmentioning
confidence: 99%
“…Illness and death of a parent will affect any child deeply, but especially infants and preschool children who are entirely dependent on their primary caregivers [27]. Studies have demonstrated comparatively poor health among young children with caregivers unwell with HIV/AIDS [28],[29], and under-nutrition has been identified as the key underlying cause of children's deaths, especially in relation to infectious disease [30]. Thus, when a mother becomes very ill and is unable to care for and feed her child, whether by breastfeeding or providing substitute or complementary feeding, the risks to the child rise substantially.…”
Section: Discussionmentioning
confidence: 99%
“…These barriers include their need to care for sick parents;24 emotional scarring related to parental death;25 and discrimination within classrooms and the community 8. For orphaned children, school-work is most likely supervised by an older sibling, or to be unsupervised, or less likely to be supervised by a caregiver,26 which can also contribute to poorer school performance. Our findings indicated a 12% drop in self-reported school performance after parental illness or death.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, after the death of a productive member of the household, children may be forced to work greater hours to offset the loss of income, often at the expense of their schooling. The few studies that incorporate parental illness or household morbidity have found negative impacts on education (Ainsworth et al, 2005;Yamano and Jayne, 2005;Gray et al, 2006;Mishra et al, 2007). For example, work by Ainsworth et al (2005) indicates that children's schooling is most affected while a parent is ill, and then recovers after their death.…”
Section: What Evidence Relates To Expanding Assistance Beyond Orphans?mentioning
confidence: 97%
“…For example, work by Ainsworth et al (2005) indicates that children's schooling is most affected while a parent is ill, and then recovers after their death. Gray et al found that children living with a sick adult were less likely to attend school or have their school fees paid than children in healthy households (Gray et al, 2006). Limited evidence also suggests that adult mortality adversely affects education within poor households (Yamano and Jayne, 2005;Ainsworth et al, 2005).…”
Section: What Evidence Relates To Expanding Assistance Beyond Orphans?mentioning
confidence: 98%